Rahn in the Perspective of the Four Schools and Their Implementation in Sharia Pawnshop Institutions in Indonesia - Faqeh, Achmad (Institut Agama Islam YPBWI Surabaya, 2025)
Islam provides economic concepts that emphasize justice and mutual benefit, among them Rahn (Islamic pawning), a lending solution based on the principle of mutual assistance (ta'awun). In this context, Rahn establishes mutual trust and security between the creditor (rahin) and the debtor (murtahin), where the pawned object serves as collateral against default. The aim of this article is to analyze the ruling of Rahn from the perspective of the four schools of Islamic jurisprudence and how this concept is implemented in Sharia Pawning Institutions in Indonesia. This research uses a library research method by analyzing primary and secondary sources. The main finding reveals a fundamental similarity in the legality of Rahn among the four schools, despite minor differences regarding the ownership and utilization of the pawned object. Practically, the implementation in Indonesian Sharia Pawnshops has successfully adapted the Rahn fiqh framework, making it a just and interest-free (riba) alternative. The main contribution of this study is to enrich Islamic scholarly discourse in muamalah (transactions) and provide a theoretical-practical guide on the sharia-compliant mechanism of Rahn in modern financial institutions.